The Use of Quartet Card Learning Media in Social Studies Subjects in Elementary School: Systematic Literature Review - Harahap, Bahani Permata (Berpusi Publishing, 2024)
This research discusses the importance of education in developing students' potential with a focus on Social Studies. Although social studies has an important role in shaping students' social understanding, it is often considered only as a subject that requires memorization. One of the Actions to improve the effectiveness teaching is by using interesting and informative Quartet Card media. The purpose of this research is to conduct a literature review related to the implementation of quartet card media in elementary schools in social studies learning. The method used is the SLR (Systematic Literature Review) method. Data collection was done by documenting and reviewing all articles related to the use of quartet card learning media in social studies subjects in elementary schools published between 2019 and 2024. There are six articles used in this research obtained through Google Scholar. The results showed that the implementation of quartet card media made a positive contribution to teaching and learning activities achievement of students' social studies learning achievement in elementary school. This learning The media doesn't just fix the learn process by making learners more active and communicative, but also creates a fun learning environment.